Pengaruh Ki Sarmidi Mangoensarkoro Dalam Lahirnya UU Pendidikan Nasional Pertama Dan Perkembangan Pendidikan Di Indonesia - Putri, Nurul Nabila (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2023)
Ki Sarmidi Mangoensarkoro was a significant figure in the field of education during the National Movement era. He was one of the individuals trusted by Ki Hajar Dewantara to design a new curriculum for the Taman Siswa educational institution. This study aims to (1) describe the role of Ki Sarmidi Mangoensarkoro in education, (2) explain Ki Sarmidi Mangoensarkoro's influence on the creation of Indonesia's first National Education Law, and (3) describe the development of education in Indonesia from the National Movement era to the present.This research employs a qualitative method. The results of this study are (1) the significant role of Ki Sarmidi Mangoensarkoro in Indonesian education, (2) the gradual improvement of education in Indonesia following the enactment of the National Education Law, and (3) the rapid advancement of education in Indonesia over time.